RESPONSIVITAS PEMERINTAH KOTA PEKANBARU DALAM PENANGGULANGAN WABAH DEMAM BERDARAH DENGUE (DBD) DI KOTA PEKANBARU TAHUN 2015 - Afrizal, Akmal; M, Erman (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2018)
The development of health in Indonesia is aimed at raising awareness, willingness, and healthy living capability for every person in order to realize a degree of health level. Demam Berdarah Dengue (DBD) is an infectious disease caused by Dengue virus. The spread of this disease in Indonesia is widespread almost evenly in all major cities, including Pekanbaru City. In 2015 an explosion of dengue fever patients so that Pekanbaru City should be set the status of Extraordinary Events (KLB).The purpose of this study is to find out how much responsiveness of Pekanbaru city government in the prevention of Demam Berdarah Dengue (DBD), related to the non-stipulation of the status of Extraordinary Occurrence (KLB) in 2015. Type of research used is descriptive research type with qualitative analysis method. This research was conducted in Pekanbaru City. Technique of data collection is done by observation, interview and documentation. While the data analysis is done by qualitative analysis. Researchers use triangulation techniques as a technique to check the validity of data.The results of the study based on service user complaints indicator, bureaucratic apparatus attitude in responding to service user's complaints, the use of service user's complaints as a reference for improvement of public services, government action in providing service and placement of service users in the prevailing service system indicates that government responsv less in facing DBD . This is evidenced by the non-stipulation of the status of Extraordinary Events (KLB), in addition to preventive efforts undertaken by the government is not optimal and evenly distributed throughout the region as well as the government's new actions felt after the fall of human lives.Keywords: Responsiveness, Demam Berdarah Dengue (DBD)